A Case Report on Euthanasia of a Rescued Horse Using Xylazine Hydrochloride and Thiopental Sodium (Research in Agriculture Livestock and Fisheries, 2022)
Veterinary professionals are still looking for a suitable method of euthanasia that causes an easy death of animals with minimum pain, fear, and suffering. The present study describes a method of euthanasia in rescued horses using xylazine hydrochloride and thiopental sodium. The study was conducted at Veterinary Teaching Hospital, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh. Xylazine hydrochloride (0.1 mg/kg; 20mg/ml) and thiopental sodium (10 mg/kg; 25% solution) was administered intravenously to the horse. The horse rapidly became unconscious and died within 4 minutes without any signs of excitement. This method can be practiced as an easy and convenient method of euthanasia of horses.Vol. 9, No. 2, August 2022: 213-219